Book Review: Jandrić, Petar and Damir Boras (eds). 2015. Critical Learning in Digital Networks. (Concept: The Journal of Contemporary Community Education Practice Theory, 2016)
In academia and beyond it is fashionable to claim to be critical and to name one’s own approach critical or even to take the form of critical theory. For example, searching in the Social Science Citation Index for the term critic (which includes search terms such as critical, critic, criticism) in the title of academic outputs for different timespans indicates this trend: 1986-1995 = 6,815 hits, 1996-2005 = 7,918 hits and 2006-2015 = 15,224 hits. Critique is a widely used and accepted term in academia. But what do we mean by critique, critical thinking and critical theory? There are several definitions of critique, and these vary in their understanding of critical thinking and come to quite different conclusions on both theoretical and political levels.